Inverser la classe : quelles expériences ? Analyse de l'activité des élèves - Valérie Lussi Borer; Alain Muller; Stéphanie Rubi (Nantes Université, 2022)
This contribution is part of a multidisciplinary collective research project on the transformation of the activity of teachers and students in the context of the "flipped classroom". Based on semi-directive interviews and self-confrontations conducted with teachers and their students, data from student interviews were analyzed using the learning registers proposed by Elisabeth Bautier and Patrick Rayou crossed with Charles Sanders Peirce's semiotics. The first results show differences between the registers that the students mobilize according to the nature of the interview, as well as in the articulation of the registers. The combination of semi-directive interviews and self-confrontations opens up promising methodological perspectives, allowing both students to express their activity in a richer way and researchers to better apprehend the experience lived by the students.